PENGUATAN DASAR NEGARA MELALUI PENYULUHAN PANCASILA PADA MAHASISWA - Rayno Dwi Adityo (LPPM Universitas Islam 45 Bekasi, 2022)
The attempt of removes Pancasila as a basis of Indonesian still continued and almost being targeting every element of society. The target households was not the just general public like before, but those young generations such as academicians like college students. Therefore, in this community devotion programe, the hightlights is on counseling Pancasila in an effort to strengthen the state foundation for college students. A method of implementation of the devotion adopting counseling with a pattern discourse or dialogue. The results of the activity have added to the insight of student participants about the dynamics of the history of Pancasila from multiple perspectives, marked by the active response of students during the discussion process. Increasing the basics of Pancasila as a meeting point with the children of the nation's, there is concern that Pancasila as the basis of the state in its implementation has not been maximized so that it still requires the role of every citizen to socialization. Realizing the importance of understanding Pancasila returned to its citizens. In conclusion, counseling on strengthening the basis of the state is important and is carried out with various perspectives so that it can add to the public's knowledge of the importance of Pancasila and show that awareness of Pancasila cultivation has not been maximized so it requires the participation of all to continued so might Pancasila relevant all off the time.